AB0782 Systemic sclerosis patients with concomitant psoriasis: a proof-of-concept pilot study. (12th June 2018) - Magnani, L.; Bajocchi, G.; Chiarolanza, I.; CAruso, A.; Aldigeri, R.; Salvarani, C.
Abstract : Background: Psoriasis and Systemic Sclerosis (SSc) are chronic inflammatory diseases characterised by a systemic immunological response which is mainly driven by activated T helper (Th) Th1/Th17 lymphocytes.. 1, 2 Further, genome-wide association studies (GWAS) in SSc have demonstrated an association at PSORS1C1, the same gene linked to psoriasis susceptibility 3 Objectives: Evaluate the statistical significance of a clinical correlation between Scleroderma and Psoriasis Methods: From April 2014 to April 2017, we enrolled 180 consecutive patients with a diagnosis of SSc fullfilling 2013 ACR/EULAR classification criteria. Patients with Localised Scleroderma (Morphea) had to have a diagnostic skin biopsy before being included. Patients satisfying VEDOSS criteria 4 were also included. Patients with psoriasis had a dermatologist-prooven diagnosis. Results: 11/180 (6.1%%, 95% IC:0.03–2.9) with scleroderma had a dermatologist-proven diagnosis of Psoriasis, and 23 patients (12.7%) had a family history of Psoriasis in a first-degree relative. For all the psoriatic patients except one, BMI was calculated; 50% had a BMI of >20 (average: 23.7). A metabolic syndrome was present in 3 out of 11 (27.2%), and in ten patients there were data available to calculate the presence of average moderate cardiovascular (CV) risk (11.5%). Finally, 3/11 patients (27.2%) had Psoriatic Arthritis (CASPAR classification criteria). In all 11 patients, Psoriasis was defined as mild (PASI ≤10). 5 The average value of modified Rodnan Skin Score (mRSS) was curiously low (0.5), [limited cutaneous (lcSSc) 5 patients, Morphea 3 patients, Very Early Systemic Sclerosis (VEDOSS) 2 patients, and diffuse cutaneous disease (dcSSc) 1 patient. Anticentromere antibodies (ACA) were detected in 5/11 patients; antinuclear antibodies, with negative extractable nuclear antigens in 4/11; Anti-topoisomerase I were found in two cases. Conclusions: Psoriasis was significantly associated with SSc (p=0.014), with a 2-fold higher frequency than that observed in general population (3%). Psoriasis +SSc, represent a further increased risk of CV disease. Th17 seems to play a crucial role in the pathogenesis of both diseases. References: [1] Fava A, Cimbro R, Wigley FM, et Al. Frequency of circulating topoisomerase-I specific CD4 T cells predicts presence and progression of interstitial lung disease in scleroderma Frequency of circulating topoisomerase-I specific CD4 T cells predicts presence and progression of interstitial lung disease in scleroderma. Arthritis Research & Therapy2016; (18)99:1–12. [2] Lei L, Zhao C, Qin F, He Z-Y, Wang X, et al. Th17 cells and IL-17 promote the skin and lung inflammation and fibrosis process in a bleomycin-induced murine model of systemic sclerosis. Clin Exp Rheumatol2016; 34 (S 100): S14-S22. [3] Allanore Y, Saad M, Dieude P, et al. Genome-Wide Scan Identifies TNIP1, PSORS1C1, and RHOB As Novel Risk Loci for Systemic Sclerosis. PLoS Genetics2011; (7)7: 1–13. [4] Minier T, Guiducci S, Bellando-Randone S Preliminary analysis of the very early diagnosis of systemic sclerosis (VEDOSS) EUSTAR multicentre study: evidence for puffy fingers as a pivotal sign for suspicion of systemic sclerosis. Ann Rheum Dis2014;73(12):2087–93. [5] Marks R, Barton SP, Shuttleworth D, Finlay AY. Assessment of disease progress in psoriasis. Arch Dermatol1989;125:235–40. Disclosure of Interest: None declared